Franklin Building at 17 Milk Street, ca. 1875 - Unknown (Tufts Archival Research Center, 2005)
Elevated view southwest of the Lincoln Building, located at 17 Milk Street between Washington Street to the west and Hawley Street to the east. Signage adorns the facade of the Lincoln Building, which faces north towards Milk Street. The northeast corner of the Transcript Building is visible along the right side of the carte-de-visite. The facade of the Goddard Building is visible along the left side of the carte-de-visite. Designed by Peabody and Stearns, 1874 3 13/16 x 2 1/4, 4 1/16 x 2 7/16 overall Cartes-de-visite